Contribution of cotranslational folding to the rate of formation of native protein structure. - Fedorov, A N (1995)
To compare the process of protein folding in the cell with refolding following denaturation in vitro, we have investigated and compared the kinetics of renaturation of a full-length protein upon dilution from concentrated urea with the rate of folding in the course of biosynthesis. Formation of enzymatically active bacterial luciferase, an alpha beta heterodimer, occurred 2 min after completion of beta-subunit synthesis in an Escherichia coli cell-free system. Renaturation of urea-denatured beta subunit, either in the presence of the cell-free protein synthesis system or in buffer solutions, proceeded more slowly. Cellular components present in the cell-free protein synthesis system slightly accelerated the rate of refolding of urea-unfolded beta subunit. The results indicate that the luciferase beta subunit begins the folding process cotranslationally and that cotranslational folding contributes to the rapid formation of the native structure in the cell.